Effect of antimethanogenic garlic-derived compounds on amylolytic and xylanolytic activities in the rumen - Martínez G.; Abecia L.; Martín-García A.I.; Ramos-Morales E.; Molina-Alcaide E.; Yáñez Ruiz D.R. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
This work assessed the effect of adding two antimethanogenic garlic-derived compounds on in vitro rumen amylolytic and xylanolytic activities. A 12-day trial was performed using a continuous-culture system inoculated with rumen fluid from goats. At the end of the trial, a subsequent experiment was carried out by incubating the fermenters’ content in batches culture to measure methane production over 24 h. The additives and doses tested were control (without additive), propyl propane thiosulfinate (PTS, 200 μl/L), diallyl-disulfide (DDS, 80 μl/L) and bromochloromethane (BCM, 160 mg/L) as positive control. The incubated substrate consisted of 50:50 alfalfa hay:concentrate mix. After 10 days of adaptation samples of the fermenters’ contents were collected at 0, 2 and 4 hours after the morning feeding and the activity of amylase and xylanase enzymes quantified. In batch cultures, the addition of PTS and BCM resulted, in a reduction (P<0.001) of methane production of 40 and 96% respectively, while DDS did not have an effect (P=0.575), compared to control. In continuous-culture a reduction (P<0.05) of xylanase activity in samples treated with PTS at all sampling times was observed compared to the control, while amylase activity was not affected (P≥0.243) by any garlic compound. On the contrary, and despite its potent anti-methanogenic effect, BCM did not affect (P≥0.647) xylanase activity but increased (P<0.05) amylase activity at 2 hours compared to the control. Our results suggest that the reduction of methane synthesis in the rumen by some garlic-derived compounds may be accompanied by a detrimental decrease in xylanase activity and might compromise fermentation and intake.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)